Effect of Dexmedetomidine on Hyperdynamic Responses During Electroconvulsive Therapy: A Randomized Double-Blind Crossover Study - Simran Nathani; Neha Panse (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Electroconvulsive therapy (ECT) is always followed by a transient vigorous pressor response in terms of raised pulse rate and blood pressure. Several anesthetic agents have been used to blunt this transient hyperdynamic response. Objective: We conducted this study with the primary aim to evaluate the efficacy of dexmedetomidine in blunting the hyperdynamic response following ECT. Secondly, we aimed to study if the administration of dexmedetomidine causes any alteration in duration of ECT seizures and any other untoward effects. Methods: This is a crossover randomized control study that included 35 patients who were scheduled to undergo 4 cycles of ECT and were ready to participate in the study. Each patient was included in the study for 2 cycles of ECT. Each patient acted as a control for themselves, and hence any bias based on patient selection was avoided. Group A: 0.5 mcg/kg dexmedetomidine in 100 ml saline was administered 15 min before ECT. Group B: 100 ml of 0.9% saline was administered 15 min before ECT. We evaluated the variations in patients’ heart rate and blood pressure, duration and intensity of motor seizures, recovery parameters & side effects, if any. Results: Dexmedetomidine significantly reduced heart rate and blood pressure during the early post-ECT period compared with placebo (p<0.001), effectively attenuating the hyperdynamic pressor response. No significant differences were observed in motor seizure duration or recovery parameters between the groups. Bradycardia requiring intervention occurred in one patient receiving dexmedetomidine. Conclusion: Dexmedetomidine effectively blunts the hyperdynamic pressor response following ECT without altering the motor seizure characteristics; thus, it is recommended as a safe premedicant before ECT without affecting the therapeutic efficacy of ECT.